The Effects of Hall and Joule Currents and Variable Properties on an Unsteady MHD Laminar Convective Flow Over a Porous Rotating Disk with Viscous Dissipation - Sattar, Abdus; Ferdows, Mohammad (IntechOpen, 2012)
None